Pengembangan Digitalisasi Marketing Usaha UMKM Untuk Meningkatkan Mengembangkan UMKM Masyarakat - Iqbal Anaqi; Dzikri Kurniawan; Tiara Putri Marcela; Devi Claudia Vanessa Jorger; Prima Nasrul Aziz; Nur Suranti Madu Sukmah; Reiga Ritomiea Ariescy (STIKes Ibnu Sina Ajibarang, 2023)
Micro, Small Enterprises, dUMKM) play an important role in the community's economy, especially in creating jobs and driving economic growth. However, MSMEs often face challenges in dealing with increasingly fierce competition and changes in market trends. In the digital era that continues to develop, the development of digitalization of MSME businesses has become an urgent need to increase their competitiveness. The development of digitalization of MSME businesses opens up great opportunities for business growth and development. By using digital technology and online platforms, MSMEs can expand their market reach and reach potential consumers in various regions. Through digital marketing, MSMEs can promote their products or services more efficiently than traditional methods. In addition, by leveraging digital data and analytics, MSMEs can better understand consumer behavior and optimize their marketing strategies. However, the development of digitalization of MSME businesses also faces several challenges. One of them is limited access and understanding of digital technology. Many SMEs do not have sufficient knowledge or resources to utilize technology effectively. In addition, data security and privacy are important concerns for MSMEs in adopting digitization. MSMEs also have to face increasing competition from large companies that have greater resources to invest in digital technology.